Maximal Ideal Graph of Zn - M Azeez, Nigar; Fryad H. Abdulqadr (Zanco Journal of Pure and Applied Sciences, 2026)
In this paper, we present the structure of the maximal ideal graph of the ring . Several graph properties are given including completeness, planarity, separability. Furthermore, we show that is Hamiltonian, and Eulerian under certain conditions. We also compute the degree of vertices, size, circumference, girth, and clique number of for specific types of n. Finally, we find Hosoya polynomial of which depends on both degree of vertices and size of the graph for certain values of n.